Mobilising the walking-with technique to explore mundane consumption practices: practical and theoretical reflections - Mak, Connie K.Y.; Lai, Ai Ling; Tsaousi, Christiana; Davies, Andrea (My University, 2022)
Purpose: Consumer studies drawing on interpretative approaches have tended to rely on sedentary interviews, which the authors argue are ill-equipped to capture the embodied, tacit and pre-reflexive knowledge that conditions routinized practices. This paper aims to provide practical and theoretical framing of the walking-with technique, in particular, with reference to practice theories. Specifically, this paper draws on Bourdieu’s concept of the “habitus” to illustrate the “workings” of the habituated body in performing routine consumption. Design/methodology/approach: This paper used the walking-with technique to elicit “mobile stories” with senior executives in Hong Kong. This paper explored how walking to and from work/lunch/dinner can open up culturally and historically embodied narratives that reflect evolving consumption practices throughout participants’ professional trajectories. Findings: This paper demonstrates the uses of the walking-with technique by illustrating how embodied narratives foreground the pre-reflexive practices of mundane consumption. This paper illustrates how walking as a “mobile mundane practice” can expand a researcher’s horizon of understanding, enabling them to “fall into the routines of participants’ life”, “get into grips with participant’s temporal (time travel portal) and cultural conditioning” and “co-experience and empathise with participants through bodily knowing”. The authors argue that walking-with necessarily implies an inter-subjective sharing of intermundane space between the researchers and the participants. Such a method is therefore conducive to engendering co-created embodied understanding-in-practice, which the authors argue is accomplished when there is a fusion-of-habituses. Future applications in other consumer contexts are also discussed. Practical implications: The walking-with technique embeds data collection in the day-to-day routes taken by participants. This does not only ease the accessibility issue but also render real-life settings relevant to participants’ daily life. Originality/value: Despite receiving growing attention in social science studies, the walking-with technique is under-used in consumer research. This paper calls for the need to mobilise walking-with as a method to uncover practical and theoretical consumer insights in a way that allows for embodied and performative knowledge (know-how) to emerge.
Keywords: Practice theories; Bodily knowing; Habitus-in-motion; Narrative time travel portal; Understanding-in-practice; Walking-with interviews